Réponses

  • Utilisateur Brainly
2014-05-04T12:09:29+02:00
Résoudre les équations :

1) 4(- 3x - 1) = 6(- 2x - 8)
- 12x - 4 = - 12x - 48
- 12x + 12x = - 48 + 4
0x = - 44
Pas de solution

2) - 5(- 4x - 7) = - 20x + 35
20x + 35 = - 20x + 35
20x + 20x = 35 - 35
40x = 0
x = 0
2014-05-04T12:14:49+02:00
1) 4 (-3x-1)=6 (-2x-8)
-12x -4 = -12x -48
12x +12x = -48+4
0 = -44

ce qui n est pas possible donc pas de solution


2) -5 (-4x-7)=-20x+35
20x +35 = -20x +35
20x +20x = 35 -35
40x =0
x = 0

donc solution x=0